Allosuckling in domestic hair sheep: a rare behavior associated with multiple births and male lambs - Pérez-Torres, Libia; Orihuela, Agustín; Herrera-Haro, José; Terrazas, Angelica (Frontiers in Ethology, 2026)
Allonursing or allosuckling is a rare but an intriguing evolutionary behavior reported in several species including mammals. Despite the energy cost of lactation, females occasionally allow alien offspring to suckle, suggesting potential adaptative, physiological, or social functions. However, information on this behavior in domestic sheep, particularly in tropical hair breeds, remains scarce. To determine the frequency and the influencing factors of non-filial suckling (NFS) in Saint Croix sheep, a total of 33 hair sheep ewes and their lambs (16 singletons, 13 twins, and 4 triplets) were observed from parturition to weaning (8 weeks of lactation). All animals were kept as a group, grazing on a paddock from 0800 to 1400 hours and penned during the rest of the day. Behavioral observations were conducted three times/week (from 0800 to 1000 and from 1400 to 1600 hours), and the suckling events (S) and suckling attempts (A) from both filial and non-filial (NF) ewe–lambs pairs and the weight gain in lambs were recorded. A total of 1,664 A and 6,203 S were observed, of which 17.0% corresponded to non-filial attempts (NFAs) and 0.6% to NFS. Of the lambs, 85% displayed NFAs, while 37% displayed NFS, at least one time. The percentage of lambs that displayed NFS was affected by the following: a) multiple births—more triplets and twins than singletons [50% (6/12) and 38% (10/26) vs. 25% (4/16), p = 0.0001]; b) the sex of the lamb—more males than females [75% (25/33) vs. 30% (10/33), p = 0.0004]; and c) the time of day context—favoring PM = pen over AM = pasture (67.2% vs. 32.8%, p = 0.0075). The age of the lamb did not affect the percentage of lambs displaying NFAs or NFS. However, NFAs were more frequent in young lambs at early lactation. All ewes received NFAs, but only 49% of them allowed NFS (100% of the ewes that gave birth to triplets, 46% bearing twins, and 37% bearing singletons). Lambs that displayed more NF activities had the lowest average weight gains at weeks 2 and 6, maintaining the same tendency throughout lactation. These results indicate that NFS occurs in hair sheep, but is infrequent and needs to be investigated in the context of nutritional stress, recognition errors, or maternal permissiveness.